PENERAPAN KOMBINASI MODEL PEMBELAJARAN KOOPERATIF TIPE MIND MAPPING DENGAN MAKE A MATCH UNTUK MENINGKATKAN KEAKTIFAN SISWA PADA MATA PELAJARAN KEARSIPAN DI SMK NEGERI 3 SURAKARTA TAHUN AJARAN 2014/2015 - Nur Rahmi Akbarini; C Dyah Sulistyaningrum Indrawati; Anton Subarno (JIKAP (Jurnal Informasi Dan Komunikasi Administrasi Perkantoran), 2016)
The objective of this research is to improve the activenessin Archive subject matter of the students in Grade X of OfficeAdministration of State Vocational High School 3 of Surakartathrough the application of combination of the cooperative learningmodel between the mind mapping type and the make a match type.The type of research conducted by the researchers is theClassroom Action Research (CAR). This research used theclassroom action research with two cycles. Each cycle consisted ofplanning, implementation, observation, and reflection. The subjects of research were 32 students grade X department of office administration of State Vocational High School 3 of Surakarta. Thedata sources of research were the subject matter teacher and thestudents. Techniques of data collected trought observation,documentation and interview method. The data were analyzed byusing the descriptive comparative technique of analysis. The result ofresearch shows that the application of combination of the cooperativelearning model between the mind mapping type and the make a matchtype can improve the student‟s activeness in archive subject matter asmuch as 53.75%. Prior to the treatment the students‟ activeness is31.26%. Following the treatment, it becomes 55.01% in Cycle I and85.01% in Cycle II. In addition, the percentage of each aspect of thestudents‟ activeness also improves as much as 50%. Prior to thetreatment, the percentage of the visual aspect activities is 34.38%.Following the treatment, it becomes 56.26% in Cycle I and 84.38% inCycle II. The percentage of the oral aspect activities improves asmuch as 59.37%. Prior to the treatment, the percentage of the oralaspect activities is 2.88%. Following the treatment, it becomes46.88% in Cycle I and 81.25% in Cycle II. The percentage of thedrawing aspect activities improves as much as 87.51%. Prior to thetreatment, the percentage of the drawing aspect activities is 0%.Following the treatment, it becomes 53.13% in Cycle I and 87.51% inCycle 2. The percentage of the mental aspect activities improves asmuch as 56.26%. Prior to the treatment, the percentage of the mentalaspect activities is 31.25%. Following the treatment, it becomes59.38% in Cycle I and 87.51% in Cycle II. The percentage of the emotional aspect activities improves as much as 46.87%. Prior to the treatment, the percentage of the emotional aspect activities is 37.51%. Following the treatment, it becomes 59.83% in Cycle I and 84.38% in Cycle II. Thus, the application of combination the cooperative learning model between the mind mapping type and the make a match type can improve the activeness in Archive subject matter of the students in Grade X of Office Administration of State Vocational High School 3 of Surakarta.